Strategi Guru Menanamkan Nilai-Nilai Akhlak Dalam Kehidupan Beragama Siswa Di SMP Plus Anbata - Sadiyah, Nadira (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
There are two objectivies of this study, namely the strategy used by the teacher in instilling moral values in the religious life of students at SMP Plus Anbata and the obstacles faced by teachers in instilling moral values in the religious life of students at SMP Plus Anbata. This research uses qualitative research methods through interview observations and document review. Qualitative research is a research process that produces descriptive data in the form of written or spoken words of people and observable behavior about a persons’s life, stories, behavior, as well as about organizational functions, social movements or reciprocity. Qualitative research is research that emphasizes what happens in the field. In qualitative research, the main key in data collection is the naturalness of the data sources obtained by researchers throught field research. The data sources obtained describe social reality in the form of words which will later be obtained from observations and interviews as well as pictures that become documentation or documentation studies that are not in the form of numbers. The results of this study are that the teachers’s strategy instills moral values in religious life at Anbata Plus Middle School. There are disciplinary rules set at Anbata Plus Middle School, there is learning about morals in the classroom, educators make themselves role models or examples. Learning outside of formal learning. There are restrictions on sanctions, social factors of students, parental factors, lack of discipline of studentds, lack of educators who foster students and educators who are not yet simultaneous in instilling moral values. There is supervision, there is the application of rules or sanctions, giving a good example, getting students to pray in congregation at the prayer room, doing good cooperation with students, integrating moral values in the learning process and the prayer room, doing good cooperation with students, integrating moral values in the learning process and educators making student reports.